Assessment and recommended treatment options for acne. Issue 19 (5th October 2014) - Cuddy, Laura; Coulson, Ian
<x xml:space="preserve">Abstract</x> Acne can have a significant social and psychological impact, and early and appropriate treatment is key to reducing the risk of permanent scarring. Our Drug review provides a brief overview of clinical assessment and discusses the available treatment options, followed by sources of further information and an analysis of the prescription data.